(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The article tries to shed some light on the Corporate Social Responsibility (CSR) activities undertaken by the top Indian manufacturing companies to combat the social, economic and health challenges emanated from the COVID-19 crisis. Effort was also made to map the CSR activities undertaken during this pandemic situation with the mandated list of CSR activities under Schedule VII of Companies Act, 2013 and Sustainable Development Goals (SDGs) in general using Content analysis technique. The outcome of the study revealed that majority of the selected Indian manufacturing companies have undertaken various preventive and mitigation measures for enabling the stakeholders to tide over the crisis which can be mapped with Clauses i, v and ix of Schedule VII of Companies Act, 2013 and SDGs 2, 3, 8 and 17.